The impact of the COVID-19 pandemic on nostalgic social media use - Xiang, Peng; Chen, Lijuan; Xu, Fuming; Du, Shasha; Liu, Mingxuan; Zhang, Yimeng; Tu, Jiayu; Yin, Xiaoyuan (Frontiers in Psychology, 2024)
As a retrospective investigation, this study aimed to determine whether the outbreak of the COVID-19 pandemic substantially increased nostalgia engagement on social media, namely nostalgia social media use. To this end, interrupted time series analysis (ITSA) using a segmented regression model was performed to examine the changes in the weekly volume of searches for nostalgic songs on Douyin (the Chinese version of TikTok), as a proxy for nostalgic social media use, before and after the lockdown of Wuhan (signaled the start of the pandemic on a national scale in China).Across the study period (January 1, 2019 to February 28, 2021), an immediate and significant increase in nostalgic social media use was observed when the pandemic initially started (95% CI = [47314.30, 154969.60], p ˂ 0.001) compared with the prepandemic baseline. The implications and limitations of this work were discussed.